Neurobehavioral, Neuromotor, and Neurocognitive Effects in Agricultural Workers and Their Children Exposed to Pyrethroid Pesticides: A Review - Lucero, Boris; Muñoz-Quezada, María Teresa (Frontiers in Human Neuroscience, 2021)
In recent years, pyrethroids have emerged as the least toxic alternative to combat insect pests, however, some laboratory studies and in children show that they present degrees of toxicity and neurobehavioral effects similar to other pesticides such as organophosphates. The purpose of this review is to systematize and analyze the epidemiological scientific evidence from the PubMed database on the effects of occupational exposure to pyrethroid pesticides on the neurobehavioral and neurocognitive functioning of agricultural workers. The results show that in 66% of the studies reviewed (n = 9), agricultural workers or their children occupationally exposed to pyrethroid pesticides have a higher risk of presenting difficulties in their neurocognitive or neurobehavioral performance, mainly associated with attention and speed problems processing. Although the research presented in this review is few, the level of quality of the studies and the evidence collected provide antecedents that confirm risk in the neurocognitive health of agricultural workers due to occupational exposure to pyrethroids. More research is required associated with the subject, regulating the sale, training workers and monitoring possible risks to human health.